Loyalty Is Reviewed From Competency, Organizational Culture, Work Environment And Rewards: Study On Working Occupational Therapists At A Hospital In The Surakarta Region - Muhtar, Basuki Sukandaru; Sudarwati, Sudarwati; Istiatin, Istiatin (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Loyalty in Terms of Competencies, Organizational Culture, Work Environment, and Rewards (Study of Hospital Occupational Therapists in the Surakarta). This study aims to determine and explain the effects of Competencies, Organizational Culture, Work Environment, and Rewards on Hospital Occupational Therapists in Surakarta. The population is all Occupational Therapists who work in Hospitals in Surakarta, the number of which is 37. The sampling technique uses the census method with a total sample of 37 respondents. Data collection using a questionnaire. Data analysis technique used statistical analysis, namely multiple linear regression test, F test, t test, and the coefficient of determination. The results of the study show that competence, organizational culture, work environment, and rewards have a positive and significant effect on the loyalty of hospital occupational therapists in the Surakarta area. This means that the higher the level of competence, organizational culture, work environment and rewards, the higher the employee loyalty, conversely the lower the level of competence, the lower employee loyalty can be. Competency, Organizational Culture, Work Environment and Rewards variables contributed to Loyalty by 57.1% while the remaining 43.9% was explained by other variables not proposed in this study. Suggestions from this research, Hospitals need to selectively provide improvement programs competence, rewards, and opportunities to practice Occupational Therapy by applying Organizational Culture at work in a conducive work environment.